DINAMIKA SIRKULASI ELITE PADA PEMILIHAN KEPALA DAERAH KABUPATEN SIAK PROVINSI RIAU TAHUN 2024 : (Studi Promosi Afni Zulkifli sebagai Bupati Terpilih) - Ruth Agnesia Sembiring (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This research examines elite circulation in the 2024 Siak Regency Election, namely the promotion of Afni Zulkifli (Afni Z) from bureaucratic authority to electoral authority. For more than a decade (2011-2024) Siak Regency was led by a regent from a bureaucratic background. This continued until the 2024 election, where all three regent candidates came from the bureaucracy. Afni Z won the election by a margin of 224 votes from the incumbent and led to a lawsuit from her rival. The results of the 2025 Re-voting (PSU) again won Afni Z as Regent of Siak for the 2025-2023 period. Qualitative research type description is used in this research, with data collection techniques through literature study and observation of mass media and social media. The results of this study use elite circulation theory. The results showed that Afni Z's promotion was caused by 3 things, namely: 1) historical development (the two-way communication capacity she gained from her career as a journalist, academic and ministerial expert); 2) relations with the community in Siak District; and 3) the support of two former Siak Regents and a former Riau Governor who encouraged changes in people's choices during the elections (to be open to new elites from the national scope bureaucracy, not incumbents or elites from the local bureaucracy). Of these 3 things, the first point and the second point are the things that most contribute to the promotion of Afni Z in achieving electoral power.